Between Manuscript and Printed Book: Problem of Figurative Sources in the French Books of Hours in the End of the 15th — First Third of the 16th Centuries - Subbotina, Olga V. (Actual Problems of Theory and History of Art, 2019)
The French printed Books of Hours dated to the end of the 15th — early 16th century can be viewed as unique items. Their connection with handwriting tradition makes them outstanding. This correlation concerns both their iconography and decorative design. The transitional character of this type of books determined particular approach to the text, decoration and iconographical models. Subsequently it also generated a lot of discussions about these books: from their titles and genesis to attribution and methodological problems. The similarity of Book of Hours’ contents to that of other books of prayer and liturgical books, such as Breviary or Psalter with supplement, could influence the images. The resulting problem of migration and transformation of iconographical models in different French typographies is one of the most serious and interesting in studying the book engraving of this period. The visual similarities between manuscripts and printed Books of Hours can be detected not only in the decorations, ornaments and letters, but also in large engraved pictures ranging from images imitating the marginalia in the margins of manuscripts and “miniaturized engravings” to iconographical models and programmes which had been transferred from manuscripts to printed books. The present paper, basing on the materials from Saint Petersburg libraries, analyses some connections between illuminated liturgical books and codices with engravings, as well as researches some debated points concerning the early French printed Books of Hours.